Effect of Prophylactic Use of Intranasal Oil Formulations in the Hamster Model of COVID-19 - Rizvi, Zaigham Abbas; Tripathy, Manas Ranjan; Sharma, Nishant; Goswami, Sandeep; Srikanth, N; Sastry, J. L. N.; Mani, Shailendra; Surjit, Milan; Awasthi, Amit; Dikshit, Madhu (Frontiers in Pharmacology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection initiates with viral entry in upper respiratory tract leading to coronavirus disease 2019 (COVID-19). Severe COVID-19 is characterized by pulmonary pathologies associated with respiratory failure. Thus, therapeutics aimed at inhibiting entry of the virus or its internalization in the upper respiratory tract, are of interest. Herein, we report the prophylactic application of two intra-nasal formulations provided by the National Medicinal Plant Board (NMPB), Anu oil and Til Tailya, in SARS-CoV2 infection hamster model. Prophylactic nasal instillation of these oil formulations exhibited reduced viral load in lungs, and resulted in reduced body weight loss and pneumonitis. In line with reduced viral load, histopathological analysis revealed a reduction in lung pathology in Anu oil group as compared to the control infected group. However, Til Tailya group did not show a significant reduction in lung pathology. Furthermore, molecular analysis using mRNA expression profiling indicated reduced expression of pro-inflammatory cytokines genes, including Th1 and Th17 cytokines for both the intra-nasal formulations as a result of decreased viral load. Together, the prophylactic intra-nasal application of Anu oil seems to be useful in limiting both the viral load and severity in SARS-CoV2 infection in hamster model.